IMPLEMENTASI IDE KESEIMBANGAN DALAM PEMBANGUNAN HUKUM PIDANA INDONESIA BERBASIS NILAI-NILAI PANCASILA - Ira Alia Maerani (UNISSULA, 2016)
Criminal Law Science consists of the Criminal Law Material (consisting of the Code of Penal (Penal Code=KUHP) and Act Outside the Criminal Code), Formal Criminal Law (Code of Criminal Law), and the Law of Criminal Execution. Code Penal (Penal Code) is derived from the Wetboek van Strafrecht voor Nederlands Indie (WvSvNI). Criminal Code (WvSNI) is a legal product